1996
DOI: 10.1111/1523-1747.ep12348937
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Expression of Sphingomyelin Acylase in Atopic Dermatitis: An Etiologic Factor for Ceramide Deficiency?

Abstract: Previously, we demonstrated that there is a marked reduction in the amount of ceramide in the stratum corneum of both lesional and nonlesional forearms in atopic dermatitis (AD), suggesting that an insufficiency of ceramides in the stratum corneum is an etiologic factor in atopic dry and barrier-disrupted skin. In this study, we investigated, as a possible mechanism involved in the ceramide deficiency, whether sphingomyelin (SM) metabolism is altered in AD as compared to normal controls. In stripped stratum co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
152
3
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 199 publications
(163 citation statements)
references
References 29 publications
7
152
3
1
Order By: Relevance
“…9). In contrast, in patients with chronic eczema or contact dermatitis, there was no significant up-regulation in the activity of SM deacylase Murata et al, 1996) or in the content of SPC in the stratum corneum compared with healthy controls (Okamoto et al, 1999), thus indicating that the up-regulated activity of SM deacylase is not a The amount of total CER (A) and ceramide-1 (acylceramide) (B) in the upper stratum corneum from patients with AD and healthy controls. The CER levels in the same individual used for correlation analysis were compared between AD and control.…”
Section: Ishibashi Et Almentioning
confidence: 72%
See 2 more Smart Citations
“…9). In contrast, in patients with chronic eczema or contact dermatitis, there was no significant up-regulation in the activity of SM deacylase Murata et al, 1996) or in the content of SPC in the stratum corneum compared with healthy controls (Okamoto et al, 1999), thus indicating that the up-regulated activity of SM deacylase is not a The amount of total CER (A) and ceramide-1 (acylceramide) (B) in the upper stratum corneum from patients with AD and healthy controls. The CER levels in the same individual used for correlation analysis were compared between AD and control.…”
Section: Ishibashi Et Almentioning
confidence: 72%
“…Thus, it is intriguing to determine the biochemical mechanism(s) underlying the ceramide deficiency because it may be linked to the physiopathogenesis of AD. In the epidermis of patients with AD, we have previously demonstrated the accentuated expression of a hitherto undiscovered epidermal enzyme, termed sphingomyelin (SM) deacylase, which was associated with the reduced ceramide mass in the stratum corneum as a result of its competition with the ceramideproducing enzyme sphingomyelinase (SMase) for the common substrate SM Murata et al, 1996). Recently, it was reported that omega-OH ceramide, an important acylceramide precursor, does not derive from SM in the mammalian stratum corneum, which suggests that it derives solely from glucosylceramide (GC) precursors (Uchida et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The SC is dysfunctional in AD as the result of one or more of the following defects: reduced levels of SC lipids. [94][95][96] acquired or genetic defects in structural proteins such as filaggrin (FLG) [97][98][99] and/or scratching that is a cardinal feature of the disease. De Benedetto et al have identified reduced expression of cldn-1 and -23, 25 and more recently cldn-4 in clinically uninvolved, nonlesional AD skin of a Northern American cohort (De Benedetto & Beck unpublished).…”
Section: Tj Abnormalities In Human Skin Disordersmentioning
confidence: 99%
“…Extremely high activities of ceramidase 7 and sphingomyelin deacylase 35 , which hydrolyze sphingomyelin into sphingophosphorylcholine and free fatty acid, have been demonstrated to be the metabolic features leading to low levels of ceramides in the SC in AD. The patients with AD in preclinical stages have altered proportions of ceramides in their skin 36,37 as a result of alterations in the activity of enzymes involved in the biosynthetic pathways of ceramide production 38,39 . IgE (IU/ml)…”
Section: Discussionmentioning
confidence: 99%